Atypical presentation and pathogenesis of a macaque lymphocryptoviral‐associated B‐cell lymphoma in a cynomolgus monkey. (3rd February 2020) - Adedeji, Adeyemi O.; Vemireddi, Vimala; Tripathi, Niraj; Durinck, Steffen; Maher, Jonathan M.; Vucic, Domagoj; Halpern, Wendy
Abstract: We report the unique pathogenesis and presentation of a rapidly progressive B‐cell lymphoma in a 3‐year‐old female cynomolgus monkey on day 50 of a 13‐week toxicity study. Clinical pathology evaluation revealed a marked leukocytosis with bicytopenia. A serum protein electrophoresis was consistent with monoclonal gammopathy. The architecture of the lymph node, spleen, and thymus were variably effaced by neoplastic cells, which also infiltrated other tissues. Immunohistochemistry of the affected tissues confirmed a predominant population of CD20+, CD79a+, CD3‐, CD68‐, and CD34‐neoplastic cells. The full data best support a diagnosis of Stage V lymphoma. Nextgen sequencing and negative prestudy serology results suggested a recent infection by macaque lymphocryptovirus (mLCV) with a unique transcriptional profile comparable with a rarely observed direct LCV infection model. This infection model might be associated with a temporary lack of an LCV antigen‐specific cytotoxic T‐cell adaptive immune response. Consistent with the established mechanisms of LCV‐related lymphoproliferation, MYC and BCL2L11 gene expression were increased and decreased, respectively. While there was no overt immunosuppression, immunophenotyping revealed the index animal had a relatively low NK cell count, which further decreased by >50% on day 24 of the study. In addition to the temporary lack of adaptive immunity, the low NK cell counts were suggestive of an impaired innate immunity to control the virally‐transformed cells and the subsequent unchecked lymphoproliferation. To our knowledge, this is the first report of a Stage V lymphoma with a unique pathogenesis in an otherwise immunocompetent cynomolgus monkey.